Al-Ghazali’s Qur’anic Sufi Hermeneutics: Study on the Story of Abraham In Search of God - Habib, Habib; Shabir, Muslich (KALAM, 2021)
The existence of hermeneutics in the Islamic world, especially in the interpretation of the Qur’an is quite problematic. Some Muslim scholars consider hermeneutics to be inapplicable in interpreting the Qur'an. moreover, historically hermeneutics has a close relationship with the tradition of biblical understanding. However, al-Ghazali in his book Jawāhir-ul Qur'ān has introduced hermeneutics-based ta'wil. This article aims to discuss the concept of the Qur’anic sufi hermeneutics developed by Imam Al-Ghazali. This study is a library research with deductive method. The research data were analyzed using Edward Husserl's phenomenology investigation to highlight the illumination of al-Ghazali's method to reach the essence of the text. The results of the study found that the discovery of the essence of the text can be achieved by mystical intuition rather than categorical intuition. Al-Ghazali asserts that individuals who seek the spiritual path are endowed with mystical intuitive abilities. Therefore, mystical experiences and spiritual readers help to uncover the hidden layers and meanings of the Qur'an. As indicated in his interpretation of Q.S al-An'am: 76-78 about Abraham's contemplation when seeking the essence of God. According to al-Ghazali, it shows how Ibrahim uses a higher faculty than the cognitive faculties of sensory perception, creativity and reason. His interpretation of Surah al-An'am relies solely on mystical intuition and cannot be understood by anyone who is not inclined towards such an interpretation.